POTENSI PENGEMBANGAN USAHA BUDIDAYA IKAN PATIN (Pangasius SP) DI DESA TATELU KABUPATEN MINAHASA UTARA - Rumimpunu, Agus; Andaki, Jardie A.; Manoppo, Victoria E.N. (AKULTURASI: Jurnal Ilmiah Agrobisnis Perikanan, 2017)
AbstractThe objective of this research was to study the potential business development  of Channel catfish farming  (Pangasius sp) in Tatelu Village North Minahasa regency.  This research was a case study and the data collected was analyzed qualitatively and quantitative. Observation and interview to Tatelu village community were used to gather the primary and secondary data. The results of the research showed that the land, fries, and feed can be used for the potential businnes development of farming  channel catfish  in Tatelu village of North Minahasa Regency. The problems faced by fish culturist included  cost, fish disease, level of community education and market demand. The skill of fish culturist needed to be develop through education , training and socialization about the benefits of fish culture. This was important due to the development of channel catfish farming had positive impact  increasing people welfare. This is important because the development of channel catfish farming has a positive impact on improving people's economi Key words : channel catfish, tatelu village, business development